Implementasi Nilai-Nilai Iman dan Taqwa dalam Mencegah Pergaulan Bebas di Kalangan Pelajar - Mujahidin, Mujahidin; Hanafiah, Nanang; Roziqin, Akhmad (An-nida: Jurnal Pendidikan Islam, 2022)
Free association among teenagers has recently become a complex problem. When viewed from certain aspects, promiscuity has a negative influence on the development and growth of personality, especially in building the young generation who are moral and pious and as the backbone of the nation. Adolescents as the young generation who inherit what has been achieved if not saved from the dangers of promiscuity will destroy the future of the youth itself, which also means that the future of the state and nation will be threatened. This study aims to obtain an overview and analyze the implementation of faith and piety in preventing promiscuity among MA Al-Husna students in Bandung. The basis for this research is 1) Theological basis: There are several verses of the Qur'an that explain the prohibition of free association with goer mukhrim, including the Qur'an of An-Nur verses 30 and 31, the Qur'an of Surah Al- Isro verse 32. 2) The philosophical foundation has written by H. Nasruddin Rajak. 3) Theoretical foundation: Abdul Mujib's theory. This research is qualitative research. Data collection in this study was carried out by means of observation, interviews, and document review. In analyzing the data, the researcher used qualitative analysis techniques with steps of data exposure, data reduction, and drawing conclusions. Based on the research that has been done, it was found that MA Al-Husna has carried out the process of implementing faith and piety in preventing promiscuity among students by planning, organizing, implementing, assessing, and trying to make solutions to the obstacles found by good. Departing from the discussion and conclusions that have been put forward, there are several implications of this research as follows: 1) The implementation of the values of faith and piety must first be instilled in the values of faith and piety in students, therefore we need relevant teaching materials as sources values of faith and piety. 2) For the successful implementation of the values of faith and taqwa in preventing promiscuity among teenagers, it is not enough just for teachers to teach the class about science about the values of faith and piety but need field workers who process the actualization of the values of faith and piety so that can prevent promiscuity, therefore an organization must be formed that occupies functions that process the implementation of the values of faith and piety that are integrated into one command. In this study, there are organizations that meet these elements, but the number of BK functions is still lacking.